Architecture and development of embedded software in the automotive environment - Doan, Štěpán; Sládek, Pavel; Maryška, Miloš; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2024)
This thesis extends the scrum methodology derived from the Scaled Agile Framework (SAFe), tailoring it specifically for the development of Embedded Automotive Software (EAS) within the automotive industry. The research embarks on an analysis of the current development environment for EAS, including a definition and classification of EAS in the automotive sector, an identification of unique challenges, practices, and other methodologies currently prevalent in automotive software development, and a review of relevant international and safety standards governing EAS. An examination of the principles of SAFe Framework and Scrum methodology provides the base and foundation for understanding their application and integration in the automotive software development landscape. This thesis further evaluates the specific requirements and critical success factors essential for the successful development of EAS, particularly focusing on the part of EAS that can use scrum, such as Infotainment systems. Through this evaluation, the research identifies key elements that the new agile methodology should address to enhance the development process of EAS using Scrum. The core contribution of this thesis is the creation of a new agile methodology that incorporates the insights gained from the analysis and evaluation phases. This methodology is designed to address the unique needs of EAS development, with a detailed outline of its components, processes, roles, and tooling. The practical applicability and effectiveness of the proposed methodology are then tested through a case study on a project "Interior Experiences," an application developed for car infotainment systems based on Android. This case study demonstrates the methodology's relevance and potential benefits in real-world EAS development projects, showing its suitability for serial production across renowned automotive brands such as Audi, Porsche, and Volkswagen.
By proposing a methodology that uses the strengths of SAFe Scrum while addressing the specific challenges of EAS development, this thesis contributes to advancing agile practices in the automotive industry, offering a pathway to more efficient, responsive, and quality-driven software development.
Vedoucí práce: Pavel Sládek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: podniková informatika [obor dipl. práce]; diplomové práce; master's theses